Elaboración de un geoportal para productos agrícolas de interés Económico en la provincia de Cotopaxi, utilizando sistemas de información geográfica. - Pucachaqui Pallo, Cristhofer David (2023)
The research project has the purpose of elaborating a geoportal for zoning products of economic interest in the province of Cotopaxi inside this is established the canton, parish, which are responsible for the production of crops that produce, the data base was obtained through the Ministry of Agriculture, livestock, aquaculture and fisheries (MAGAP), the geoportal that was developed was done through three phases: planning, development and completion was used the tool of geographic information system and ArcGis online. In the analysis of the metadata, the information that makes up the coordinates in (X, Y, Z) is established by the canton, parish, place to which it belongs with the crop that is located in a given place.